Knowledge, Attitude and Practice of Staff on Segregation of Hospital Waste: A Case Study of a Tertiary Private Hospital in Kenya - Jaccobed Wanjiku Maina (European Scientific Journal, ESJ, 2018)
This study set to find out the knowledge, attitude and practice of hospital staff in segregation of hospital waste. Specifically, the study sought to analyse how healthcare waste is segregated, what organizational factors affect the practice, knowledge on proper management of biomedical waste and the attitude of workers towards the practice. A sample size of 105 respondents was included in the study from a population of 442 members of staff. Stratified random sampling technique was used. A structured questionnaire was administered to the sample. The Statistical Package for the Social Sciences was used for the purpose of data analysis. Data was analyzed using descriptive statistical techniques. Inferences were drawn using chi-square test of significance. Results revealed that waste segregation was done across all the departments at the hospital except the accounts department. Syringes and needles made up most of the waste segregated from the various departments at the hospital. With the exception of surgical blades and needles which were disposed in yellow sharps containers, all the other healthcare wastes were disposed in any of the bins. Clear instructions and guidelines influenced the practice of waste segregation among staff at the hospital. The study recommended that training on health care waste management should be done on a regular basis. Adequate quantity of the right colour of waste disposal bags should be provided. Policies and guidelines should be introduced in order to guide and direct staff on what the institution expects of them. A waste segregation plan should be introduced.